Radioiodide Treatment of Pulmonary Metastases of Differentiated Thyroid Cancer - Němec, J.; Zamrazil, V.; Pohunková, D.; Röhling, S. (Nuklearmedizin - NuclearMedicine, 1979)
Pulmonary metastases were found in 123 out of 840 patients with thyroid cancer between 1955-1977. 87 patients with pulmonary metastases of differentiated cancer were studied in detail, including an evaluation of prognostically important factors. In 66 of them, the induction of 131I uptake in metastases was attempted, in half of them successfully. Uptake was achieved more frequently in younger subjects, in papillary cancers and in patients with fine pulmonary metastases on chest films. Survival (not corrected for age) was evaluated 10 and 15 years following the diagnosis of thyroid cancer and was found to be 29,1 % and 12,2%, respectively. Significantly higher survival rates were seen in younger patients, in patients with the fine type of pulmonary metastases, in the absence of bone metastases and, particularly, in patients with induced 131I uptake in metastases. Papillary cancers were found to have higher survival rates in males and in young subjects only, in the whole group the survival rates were independent of either microscopic type or sex. It is believed that biologic behaviour of distant (pulmonary) metastases may be influenced by radioiodide therapy.